EFFECTIVENESS OF A PROBLEM-BASED LEARNING MODULE ON SALT HYDROLYSIS IN IMPROVING STUDENT LEARNING OUTCOMES - Batu Bara, Humairoh Azhari; Mawardi, Mawardi; Akmar, Reza; Ulianas, Alizar; Suryani, Okta; Aini, Faiza Qurrata; Mulyanti, Mulyanti (FKIP USK, 2024)
This study aimed to analyze the effectiveness of the problem-based learning module on students' learning outcomes at SMAN 1 Bukittinggi. This study employed Plomp's development model. The research applies a quasi-experimental type with a non-equivalent control group design. The population includes phase F students of Class XI of SMAN 1 Bukittinggi who are studying chemistry in the 2023/2024 academic year as many as six classes. The sample was taken with a purposive sampling technique, and the selected classes XI F9 and XI F10. The test instrument was 20 multiple-choice questions. The data obtained were analyzed using the n-gain and hypothesis testing with the Mann-Whitney test. The results of data analysis obtained the n-gain value of the experimental class and control class, respectively, namely 0.74 with a high category and 0.58 with a medium category. As for hypothesis testing, the calculation of Asymps. Sig 0.05, then the learning outcomes of experimental class students are higher than those of the control class. The results showed that problem-based learning module learning on is effective in improving student learning outcomes at SMAN 1 Bukittingi.